Differentiation of Staphylococcus aureus and Staphylococcus epidermidis by PCR for the fibrinogen binding protein gene. - Babra, Charlene; Mukkur, Trilochan; Costantino, Paul; Wetherall, John; Hegde, N.; Gogoi Tiwari, Jully (American Dairy Science Association, 2013)
Mastitis is one of the most common and burdensome diseases afflicting dairy animals. Among other causes of mastitis, staphylococci are frequently associated with clinical and subclinical mastitis. Although Staphylococcus aureus is the predominant species involved, Staphylococcus epidermidis and other coagulase-negative staphylococci are increasingly being isolated from cases of bovine mastitis. Although Staph. aureus and Staph. epidermidis can be easily differentiated based on theirbiochemical properties, such phenotypic identification is time consuming and laborious. This study aimed to rapidly identify Staph. aureus and Staph. epidermidis. Accordingly, a multiplex PCR was developed and we found that a single gene encoding the adhesin fibrinogen binding protein could be used to identify and differentiate the two species. Consequently, a multiplex reaction combining a triplex PCR for Staph. aureus and a duplex PCR for Staph. epidermidis was standardized, first using bacterial cultures and then with pasteurized milk spiked with live organisms or DNA extracted fromthe organisms. The test could specifically detect Staph. aureus and Staph. epidermidis even in the presence of a dozen other organisms. The limit of detection for detecting Staph. aureus and Staph. epidermidis separately was 10 to 100 cfu/mL for simplex PCR and 104 cfu/mL for multiplex PCR. Conversely, the limit was 106 cfu/ mL by multiplex PCR for simultaneous detection of both the organisms when spiked into culture medium or pasteurized milk. Overnight enrichment enhanced the assay sensitivity 100-fold. The assay had a high diagnostic sensitivity and specificity. The application ofthe test was verified on 602 field isolates of staphylococci that had been characterized earlier by phenotypic methods. Importantly, 25 coagulase-negative isolates were identified as Staph. aureus by the multiplex PCR. The test could be adapted for use in clinical diagnostic laboratories